Noninvasive Optical Imaging of UV‐Induced Squamous Cell Carcinoma in Murine Skin: Studies of Early Tumor Development and Vitamin D Enhancement of Protoporphyrin IX Production. (25th September 2015) - Rollakanti, Kishore R.; Anand, Sanjay; Davis, Scott C.; Pogue, Brian W.; Maytin, Edward V.
Abstract: Better noninvasive techniques are needed to monitor protoporphyrin IX (PpIX) levels before and during photodynamic therapy (PDT) of squamous cell carcinoma (SCC) of the skin. Our aim was to evaluate (1) multispectral fluorescent imaging of ultraviolet light (UV)‐induced cancer and precancer in a mouse model of SCC and (2) multispectral imaging and probe‐based fluorescence detection as a tool to study vitamin D (VD) effects on aminolevulinic acid (ALA)‐induced PpIX synthesis. Dorsal skin of hairless mice was imaged weekly during a 24‐week UV carcinogenesis protocol. Hot spots of PpIX fluorescence were detectable by multispectral imaging beginning at 14 weeks of UV exposure. Many hot spots disappeared after cessation of UV at week 20, but others persisted or became visible after week 20, and corresponded to tumors that eventually became visible by eye. In SCC‐bearing mice pretreated with topical VD before ALA application, our optical techniques confirmed that VD preconditioning induces a tumor‐selective increase in PpIX levels. Fluorescence‐based optical imaging of PpIX is a promising tool for detecting early SCC lesions of the skin. Pretreatment with VD can increase the ability to detect early tumors, providing a potential new way to improve efficacy of ALA‐PDT. Abstract : Newly formed squamous cell skin cancers on the back of a hairless mouse (top panel), observed at 24 weeks after the start of a UV‐exposure protocol, selectively express high levels of protoporphyrin IX following a 4‐h application of aminolevulinate and noninvasive fluorescence detection (bottom panel).